1998
DOI: 10.4319/lo.1998.43.5.0741
|View full text |Cite
|
Sign up to set email alerts
|

A new explanation of particle capture in suspension- feeding bivalve molluscs

Abstract: Using video endoscopy, we examined water flow through the infrabranchial cavity and observed particle capture by the ctenidia (gills) of several species of suspension-feeding bivalve molluscs. We found that previously published interpretations of the particle capture process did not adequately explain our in vivo observations. Instead, we propose that particle capture in bivalves can be explained in terms of hydrosol filtration theories that have been shown to apply to a wide diversity of aquatic suspension fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 41 publications
7
48
0
Order By: Relevance
“…Particles > 4 µm are stopped and transferred to the frontal side, whereas smaller particles either follow the flow around the cirri or they are stopped by the cirri's branching cilia (Dral 1967, Moore 1971, Owen 1974, Jørgensen 1975b, 1996, Owen & McCrae 1976, Silvester & Sleigh 1984, Riisgård 1988, Beninger et al 1992, Nielsen et al 1993, Riisgård et al 1996, Silverman et al 1999. Although a mechanism based on a low particle-approach angle and direct interception at gill filaments has been proposed (Ward 1996, Ward et al 1998, this does not appear consistent with the principles of fluid dyamics (Beninger 2000, Silverman et al 2000. Based on estimates of pressure drop for flow through a laterofrontal-cirri screen (modeled as parallel cylinders of diameter 0.06 µm and spacing 1.3 µm) and creeping flow calculations, Riisgård et al (1996) found it plausible that during normal beating Larsen & Riisgård (1994) of the laterofrontal cirri the through-current passes mainly around the laterofrontal cirri in an oscillatory, unsteady, 3-dimensional pattern and that only a little flow may leak through the branching cilia.…”
Section: Cirri Trappingmentioning
confidence: 99%
“…Particles > 4 µm are stopped and transferred to the frontal side, whereas smaller particles either follow the flow around the cirri or they are stopped by the cirri's branching cilia (Dral 1967, Moore 1971, Owen 1974, Jørgensen 1975b, 1996, Owen & McCrae 1976, Silvester & Sleigh 1984, Riisgård 1988, Beninger et al 1992, Nielsen et al 1993, Riisgård et al 1996, Silverman et al 1999. Although a mechanism based on a low particle-approach angle and direct interception at gill filaments has been proposed (Ward 1996, Ward et al 1998, this does not appear consistent with the principles of fluid dyamics (Beninger 2000, Silverman et al 2000. Based on estimates of pressure drop for flow through a laterofrontal-cirri screen (modeled as parallel cylinders of diameter 0.06 µm and spacing 1.3 µm) and creeping flow calculations, Riisgård et al (1996) found it plausible that during normal beating Larsen & Riisgård (1994) of the laterofrontal cirri the through-current passes mainly around the laterofrontal cirri in an oscillatory, unsteady, 3-dimensional pattern and that only a little flow may leak through the branching cilia.…”
Section: Cirri Trappingmentioning
confidence: 99%
“…These two species possess ctenidia with a unique combination of architecture and complexity of laterofrontal (LF) ciliary tracts, which aid in particle capture (Ward et al 1998). Mussels (ca.…”
Section: Feeding Experimentsmentioning
confidence: 99%
“…Previous studies of bivalve ecological functions have ranged from highly controllable laboratory studies with short response times and no feedback loops (e.g. Wright et al 1982, Swanberg 1991, O'Riordan et al 1993, Ward et al 1998, to experiments in field flumes (Asmus et al 1992(Asmus et al , 1998, to very realistic but largely uncontrollable whole-ecosystem field studies (e.g. Dame & Libes 1993) that include all the direct and indirect interactions and feedbacks.…”
Section: Introductionmentioning
confidence: 99%